What is the idea behind peer-to-peer support in diabetes?. (January 2013) - Simmons, David; Bunn, Chris; Cohn, Simon; Graffy, Jonathan
SUMMARY  Peer support has been proposed as a means of improving the physical and mental health of people with diabetes, but what is 'peer support'? A literature review revealed that use of the term is a recent phenomenon that has gained momentum over the last two decades and refers to a plethora of interventions. Two dimensions are apparent: the nature of the support given (lying between instructing and confounding) and the interpersonal relationship created (lying between paraprofessional and companion). There is a clear tendency to confuse peer support with educational or self-management programs, and tension exists where imposed structures can inhibit the inherently unstructured nature of peer support. However, peer support can act as a useful adjuvant to service provision, providing that the flexibility inherent in allowing patients to negotiate the meaning of their experiences together is maintained.